Atmospheric parameters of Cepheids from flux ratios with ATHOS: I. the temperature scale - Lemasle, Bertrand; Hanke, Michael; Storm, Jesper; Bono, Giuseppe; Grebel, Eva K. (Astronomy and astrophysics, 2020)
Context. The effective temperature is a key parameter governing the properties of a star. For stellar chemistry, it has the strongest impact on the accuracy of the abundances derived. Since Cepheids are pulsating stars, determining their effective temperature is more complicated than in the case of nonvariable stars.Aims. We want to provide a new temperature scale for classical Cepheids, with a high precision and full control of the systematics.Methods. Using a data-driven machine learning technique employing observed spectra, and in taking great care to accurately phase single-epoch observations, we tied flux ratios to (label) temperatures derived using the infrared surface brightness method.Results. We identified 143 flux ratios, which allow us to determine the effective temperature with a precision of a few Kelvin and an accuracy better than 150 K, which is in line with the most accurate temperature measures available to date. The method does not require a normalization of the input spectra and provides homogeneous temperatures for low- and high-resolution spectra, even at the lowest signal-to-noise ratios. Due to the lack of a dataset with a sufficient sample size for Small Magellanic Cloud Cepheids, the temperature scale does not extend to Cepheids with [Fe/H] < −0.6 dex. However, it nevertheless provides an exquisite, homogeneous means of characterizing Galactic and Large Magellanic Cloud Cepheids.Conclusions. The temperature scale will be extremely useful in the context of spectroscopic surveys for Milky Way archaeology with the WEAVE and 4MOST spectrographs. It paves the way for highly accurate and precise metallicity estimates, which will allow us to assess the possible metallicity dependence of Cepheids’ period-luminosity relations and, in turn, to improve our measurement of the Hubble constant H0.